Intermediated versus Direct Investment: Optimal Liquidity Provision and Dynamic Incentive Compatibility - von Thadden, Ernst-Ludwig (Journal of Financial Intermediation, 1998)
The existing banking literature leaves largely unanswered the question: what is the viability of bank liquidity provision if investors can dynamically readjust their portfolios? To address this question, I analyze the problem of optimal liquidity provision through bank deposit contracts in a simple continuous-time equilibrium model under uncertainty. My model introduces the possibility of investors' directly investing in the market, which gives rise to a moral hazard problem in the use of deposit contracts. I argue that this can severely restrict liquidity provision and characterizes incentive-compatible deposit contracts as second-best mechanisms to provide liquidity. The analysis shows that at the optimum, liquidity provision is negatively correlated with the degree of irreversibility of the market investment opportunity. In particular, when the market investment opportunity is completely reversible, deposit contracts cannot provide any insurance against liquidity risks.Journal of Economic LiteratureClassification Numbers: D 51, D 92, G 20, G 21.